Islamic Banking Performance Based on Profitability Approach of Indonesia Malaysia Islamic Banks - Illahi, Mery Kurnia; Firdaus, Firdaus; Fakhruddin, Imam (Talaa : Journal of Islamic Finance, 2023)
The background of this research is that the strongest sharia banks in Asia are Indonesia and Malaysia, but still dominated by Malaysia. Indonesia with the largest sharia market in Southeast Asia is only in eleven and fifteen positions. This shows a huge gap in the development of the Sharia Bank in Southeast Asia. The aim of this study is to identify and analyse the differences in financial performance between sharia banks in Indonesia and Malaysia period 2016-2020. The data used in the study are secondary data obtained from the annual financial statements published by each bank. The data analysis techniques used in this study are the analysis of descriptive data, the normality test, the homogeneity test and the Mann Whitney test. The results of the study showed that the ROA variable value Sig. (2-tailed) was 0.600 > 0.05, the ROE variable of Sig. (2.-tailing) was 0.076 > 0.05 and the BOPO value of Sig.2-tailes was 0.009 < 0.05. It can then be concluded that the profitability ratio of ROA and ROE, there is no difference, while BOPO there is a difference between the financial performance of Bank Shariiah in Indonesia and Bank Syariah in Malaysia.